Hormonal regulation of the osteogenic signature in bone metastatic Castration-Resistant Prostate Cancer (CRPC) - Sankar Perumal, Sowndharya (My University, 2023)
Bone is the most preferred site for prostate cancer (PCa) metastasis which is a significant cause of cancer-related death in men. Bone metastasis in PCa typically forms sclerotic lesions, i.e., an increase in abnormal bone mass, unlike, for example, breast cancer that primarily forms osteolytic lesions, reducing the bone mass. Currently, there are only palliative treatments available for patients with bone metastatic PCa. The aim of the present study was to investigate the effects of sex hormones on osteogenic bone formation in castration-resistant prostate cancer (CRPC) using a preclinical mouse model. As a model, we used an intratibial VCaP xenograft in nude mice, mimicking the sclerotic phenotype of CRPC bone lesions. To study the contribution of adrenal-derived sex hormones, and their precursors, on the osteogenic signature, we compared sham and tumor-bearing bones in orchiectomized (ORX) and ORX+ adrenalectomized (ADX) mice. The transcriptome of the tumor-induced osteogenic signature was assessed by analyzing bulk RNA seq data annotated against the mouse reference sequence and confirming the RNA seq data with pathway analysis and RT-qPCR. The data revealed that the osteogenic signature involved in tumor-induced bone formation observed in the ORX mice was attenuated in ADX mice. This suggests that the osteogenic progression in the CRPC model used is clearly dependent on adrenal-derived factors. Altogether, the data suggest that the adrenal-derived factors, likely steroid hormones, and their precursors, critically contribute to the osteogenic progression of CRPC in vivo.
Keywords: ADX, castration-resistant prostate cancer, ORX, osteogenic, prostate cancer